Direct modulation of microglial function by electrical field - Lennikov, Anton; Yang, Menglu; Chang, Karen; Pan, Li; Saddala, Madhu Sudhana; Lee, Cherin; Ashok, Ajay; Cho, Kin-Sang; Utheim, Tor Paaske; Chen, Dong Feng (Frontiers in Cell and Developmental Biology, 2022)
Non-invasive electrical stimulation (ES) employing a low-intensity electric current presents a potential therapeutic modality that can be applied for treating retinal and brain neurodegenerative disorders. As neurons are known to respond directly to ES, the effects of ES on glia cells are poorly studied. A key question is if ES directly mediates microglial function or modulates their activity merely via neuron-glial signaling. Here, we demonstrated the direct effects of ES on microglia in the BV-2 cells – an immortalized murine microglial cell line. The low current ES in a biphasic ramp waveform, but not that of rectangular or sine waveforms, significantly suppressed the motility and migration of BV-2 microglia in culture without causing cytotoxicity. This was associated with diminished cytoskeleton reorganization and microvilli formation in BV-2 cultures, as demonstrated by immunostaining of cytoskeletal proteins, F-actin and β-tubulin, and scanning electron microscopy. Moreover, ES of a ramp waveform reduced microglial phagocytosis of fluorescent zymosan particles and suppressed lipopolysaccharide (LPS)-induced pro-inflammatory cytokine expression in BV-2 cells as shown by Proteome Profiler Mouse Cytokine Array. The results of quantitative PCR and immunostaining for cyclooxygenase-2, Interleukin 6, and Tumor Necrosis Factor-α corroborated the direct suppression of LPS-induced microglial responses by a ramp ES. Transcriptome profiling further demonstrated that ramp ES effectively suppressed nearly half of the LPS-induced genes, primarily relating to cellular motility, energy metabolism, and calcium signaling. Our results reveal a direct modulatory effect of ES on previously thought electrically "non-responsive" microglia and suggest a new avenue of employing ES for anti-inflammatory therapy.